Musical Spectra, l'espace sensible and Contemporary Opera. Issue 1 (26th April 2018) - CROSS, JONATHAN
Abstract: The appearance of the corps sonore at a key dramatic moment in Rameau's Pygmalion (1748) opens up an espace sensible (a term borrowed from Michel Leiris) where sounds derived from the harmonic series can articulate transformed temporal and spatial environments. The corps sonore – rediscovered and repurposed by the spectral movement of the 1970s – reappears in a number of twenty-first-century operas in order to animate a late-modern sense of the espace sensible . Instead of crossing a threshold towards the transcendent, the seemingly immobile corps sonore can now represent a modernist sense of loss, death, exile, ruin, and failure. Michaël Levinas's 2010 operatic reinterpretation of Kafka's Metamorphosis stands as an exemplar of the ways in which the spectrum of sound (here the voice of the 'becoming-animal' Gregor Samsa metamorphosed by electronic means) can create a 'deterritorialized' space of alienation. Liminal, spectral spaces in works by Dufourt, Grisey, Haas, Harvey, Murail, and Saariaho are also discussed.